Scanning as a Rhetorical Activity: Reporting Histories of Ether Experiments in the Johns Hopkins University Physical Seminary (1892–1913). (January 2021) - Cutrufello, Gabriel
This article reports on a study that examined papers written by graduate students in the Physical Seminary course at Johns Hopkins University (1892–1913) to investigate how students reused various visuals of the interferometer to construct narratives of late-19th-century Ether research. Their representations of the interferometer focused on the mechanics of the devices by constructing a series of textual-visual relationships, requiring that the reader scan back and forth between the written text and the accompanying visual. These multimodal texts demonstrate how the students used writing activities to create a narrative of equipment development, which highlighted the centrality of trained vision in enculturating graduate students into disciplinary writing practices in the late 19th century. Through an analysis of the specific interactions and the network of visuals the students used to reconstruct a history of Ether investigation, scholars of writing and rhetoric can see how important inclusion of equipment and its detailed discussion was to graduate writing and disciplinary enculturation in the sciences.